2010
DOI: 10.1016/j.ydbio.2009.10.016
|View full text |Cite
|
Sign up to set email alerts
|

In vivo analysis in Drosophila reveals differential requirements of contact residues in Axin for interactions with GSK3β or β-catenin

Abstract: Proper regulation of the Wingless/Wnt signaling pathway is essential for normal development. The scaffolding protein Axin plays a key role in this process through interactions with Drosophila Shaggy and Armadillo. In the current studies, we used a yeast two-hybrid assay to identify ten amino acids in Axin that are critical for in vitro interaction with Shaggy and two for interaction with Armadillo. We then generated five Axin variants in which individual putative contact amino acids were mutated and compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…However, the data strongly indicates that frizzleds, Gαo and Gαs act to position Apc2, and all except Gαs likely act through Axin as they are required for its positioning. The ability of activated and inactive forms of sgg (GSK3β) to modulate localization of Apc2-GFP and Axin-GFP are consistent with a subset of wnt signaling proteins playing a role in branch point localization as sgg can bind Axin ( kremer et al 2010 ) as well as other wnt signaling proteins. However, we do not have evidence that sgg is normally involved in branch point localization at this point because the RNAi that targets sgg had no effect in any of the assays.…”
Section: Discussionmentioning
confidence: 53%
“…However, the data strongly indicates that frizzleds, Gαo and Gαs act to position Apc2, and all except Gαs likely act through Axin as they are required for its positioning. The ability of activated and inactive forms of sgg (GSK3β) to modulate localization of Apc2-GFP and Axin-GFP are consistent with a subset of wnt signaling proteins playing a role in branch point localization as sgg can bind Axin ( kremer et al 2010 ) as well as other wnt signaling proteins. However, we do not have evidence that sgg is normally involved in branch point localization at this point because the RNAi that targets sgg had no effect in any of the assays.…”
Section: Discussionmentioning
confidence: 53%
“…For example, overexpression of Axin constructs lacking the GID in Xenopus failed to ventralize embryos, while a Drosophila Axin ΔGID protein expressed at near endogenous levels was unable to rescue embryos. Presumably, the loss of activity of these proteins was due to their inability to regulate the β-catenin destruction complex ( Fagotto et al, 1999 ; Hedgepeth et al, 1999 ; Itoh et al, 1998 ; Kremer et al, 2010 ; Peterson-Nedry et al, 2008 ). We showed that overexpression of Axin GID alone produced a phenotype reminiscent of those produced by downregulation of GSK-3β activity or overexpression of β-catenin ( Emily-Fenouil et al, 1998 ; Wikramanayake et al, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…This makes it surprisingly robust to removal of some but not all protein interaction motifs. For example, individually deleting most of APC's bCat-binding sites, Axin's bCat-binding site, or Axin's RGS domain have only modest effects in vivo (Kremer et al, 2010;Kunttas-Tatli et al, 2012;Peterson-Nedry et al, 2008;Roberts et al, 2011;Yamulla et al, 2014). However, some binding sites are essential individually (Axin's GSK-3-binding site) or when deleted in concert (AxinDRGSDArm; Peterson-Nedry et al, 2008).…”
Section: Stabilizing Destruction Complex Supermolecularmentioning
confidence: 99%